The Influence of Labor Competence, and Innovation Behavior on the Motivation for Achievement and Performance of Wooden Furniture Smes Employees in Pasuruan City - Arga Christian Sitohang; Bambang Wiwoho (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The phenomenon that occurs in the midst of wooden furniture SMEs in Pasuruan City shows that labor competence is still low, innovation behavior is less creative, motivation for low achievement and employee performance fluctuates. This study aims to determine the influence of labor competence and innovation behavior on the motivation for achievement and performance of employees of the Wooden Furniture Medium Keil Industry (IKM) in Pasuruan City. Design/Methodology/Approach: Research models with hypothesis development are derived based on literature. To provide empirical evidence, researchers conducted a survey, primary data were collected using a list of questionnaires, and saturated sampling of 50 employees. Findings: The results showed that the variable of Labor Competence had a positive effect on Achievement Motivation, while Innovation Behavior had a positive and significant effect on Achievement Motivation. However, the three variables of Manpower Competence, Innovation Behavior and Motivation for achievement have a direct effect on the Performance of Wooden Furniture IKM Employees in Pasuruan City. Practical Implications: The implications of this study are to test the perception of 50 employees of IKM Wooden Furniture in Pasuruan City. The analysis technique used is Partial Least Square (PLS). Originality/value: Papers. Type of paper: Research Paper.